Endosulfan inhibits proliferation through the Notch signaling pathway in human umbilical vein endothelial cells. (February 2017) - Wei, Jialiu; Zhang, Lianshuang; Ren, Lihua; Zhang, Jin; Yu, Yang; Wang, Ji; Duan, Junchao; Peng, Cheng; Sun, Zhiwei; Zhou, Xianqing
Abstract: Our previous research showed that endosulfan triggers the extrinsic coagulation pathway by damaging endothelial cells and causes hypercoagulation of blood. To identify the mechanism of endosulfan-impaired endothelial cells, we treated human umbilical vein endothelial cells (HUVECs) with different concentrations of endosulfan, with and without an inhibitor for Notch, N -[ N -(3, 5-difluorophenacetyl)-1-alanyl]S-Phenylglycinet-butylester (DAPT, 20 μM), or a reactive oxygen species (ROS) scavenger, N -Acetyl-l -cysteine (NAC, 3 mM), for 24 h. The results showed that endosulfan could inhibit cell viability/proliferation by increasing the release of lactate dehydrogenase (LDH), arresting the cell cycle in both S and G2/M phases, and inducing apoptosis in HUVECs. We also found that endosulfan can damage microfilaments, microtubules, and nuclei; arrest mitosis; remarkably increase the expressions of Dll4, Notch1, Cleaved-Notch1, Jagged1, Notch4, Hes1, and p21; and significantly induce ROS and malondialdehyde production in HUVECs. The presence of DAPT antagonized the above changes of cycle arrest, proliferation inhibition, and expressions of Dll4, Notch1, Cleaved-Notch1, Hes1, and p21 caused by endosulfan; however, NAC could attenuate LDH release; ROS and malondialdehyde production; apoptosis; and the expression levels of Dll4, Notch1, Cleaved-Notch1, Notch4, and Hes1 induced by endosulfan. These results demonstrated that endosulfan inhibited proliferation through the Notch signaling pathway as a result of oxidative stress. In addition, endosulfan can damage the cytoskeleton and block mitosis, which may add another layer of toxic effects on endothelial cells. Graphical abstract: Highlights: Endosulfan induces cell cycle arrest, inhibits proliferation, and causes apoptosis of endothelial cells. Endosulfan activates protein expressions in the Notch signaling pathway. Endosulfan induces toxicity of endothelial cells by activating the Notch signaling pathway. Endosulfan damages the cytoskeleton and blocks mitosis of endothelial cells. Abstract : The main finding of the present study is that endosulfan inhibits proliferation through the Notch signaling pathway and blocks mitosis in HUVECs.